Mesostigma viride Genome and Transcriptome Provide Insights into the Origin and Evolution of Streptophyta. Issue 1 (24th October 2019) - Liang, Zhe; Geng, Yuke; Ji, Changmian; Du, Hai; Wong, Chui Eng; Zhang, Qian; Zhang, Ye; Zhang, Pingxian; Riaz, Adeel; Chachar, Sadaruddin; Ding, Yike; Wen, Jing; et al.
Abstract: The Streptophyta include unicellular and multicellular charophyte green algae and land plants. Colonization of the terrestrial habitat by land plants is a major evolutionary event that has transformed the planet. So far, lack of genome information on unicellular charophyte algae hinders the understanding of the origin and the evolution from unicellular to multicellular life in Streptophyta. This work reports the high‐quality reference genome and transcriptome of Mesostigma viride, a single‐celled charophyte alga with a position at the base of Streptophyta. There are abundant segmental duplications and transposable elements in M. viride, which contribute to a relatively large genome with high gene content compared to other algae and early diverging land plants. This work identifies the origin of genetic tools that multicellular Streptophyta have inherited and key genetic innovations required for the evolution of land plants from unicellular aquatic ancestors. The findings shed light on the age‐old questions of the evolution of multicellularity and the origin of land plants. Abstract : Mesostigma viride is a single‐celled freshwater biflagellate charophyte green alga and represents the earliest diverging lineage of streptophytes. Herein, its high‐quality reference genome and transcriptome are presented, which reveal the origin and innovations of key genetic tools in Streptophyta, and shed light on the evolution of multicellularity and the origin of land plants.